Changes in remuneration and reward systems (Luxembourg, 2016)
"The use of supplementary employee reward systems has increased across Europe in recent decades, both in terms of the number of companies using them and the number of employees covered. Supplementary reward systems include performance-related pay, profit-sharing, payment by results and benefits in kind. These forms of remuneration can help to motivate and reward workers and to link pay to company results. This report examines the different types of supplementary pay schemes, their prevalence in different countries and sectors across the EU and Norway, and their relevance to different groups of employees. It also examines how systems are regulated in each country, how far they are integrated into collective agreements, and the views of social partners."